Intellectual capital and performance in the Chinese life insurance industry - Lu W.-M.; Wang W.-K.; Kweh Q.L. (2023)
This study applies the dynamic slack-based measure (DSBM) model to evaluate the performance of 34 Chinese life insurance companies for the period 2006-2010. This study also examines the relationship between intellectual capital and performance using the truncated regression approach. Our findings indicate that over the period of the study, the mean efficiency scores of life insurers are relatively stable, ranging from 0.905 to 0.973. We verify that the efficiency scores of the DSBM model differ significantly from those of the traditional data envelopment analysis (DEA) model, which supports the use of the DSBM model. Our regression analysis reveals that intellectual capitals are significantly positively associated with firm operating efficiency. Our findings corroborate prior studies which show that intellectual capital can make a company rich. In this dynamic business world, life insurers' managers should invest and fully utilize intellectual capital to gain a competitive advantage. © 2013.